2006
DOI: 10.1002/ijc.22059
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of recurrence in Ta urothelial cell carcinoma by real‐time quantitative PCR analysis: A microarray validation study

Abstract: Accurate prediction of tumor recurrence in patients with superficial urothelial cell carcinoma (UCC) might result in a significant reduction of invasive follow-up cystoscopies. A recent study identified a panel of 26 genes from a large cDNA microarray analysis of bladder tumors that discriminated between early-and late-recurring patients with superficial Ta tumors (Dyrskjøt et al., Nat Genet 2003;33:90-6). We aimed to validate this panel of genes in 44 primary Ta UCCs (23 and 21 tumors from patients with shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Unfortunately, a signature for disease recurrence prediction did not show any correlation to clinical outcome. This observation has previously been reported by another group (16). The molecular signatures were able to classify tumors correctly, although the tumors used in this study were sampled in different countries with different freezing and RNA extraction procedures.…”
Section: Discussionsupporting
confidence: 79%
“…Unfortunately, a signature for disease recurrence prediction did not show any correlation to clinical outcome. This observation has previously been reported by another group (16). The molecular signatures were able to classify tumors correctly, although the tumors used in this study were sampled in different countries with different freezing and RNA extraction procedures.…”
Section: Discussionsupporting
confidence: 79%
“…This study is a logic follow-up to identify molecular markers in very early stage of primary NMIBC that may predict its recurrence. If we define upregulated or downregulated genes of our study, several of them are common to genes published by other authors, but in general the analogy of the genes, presented here, is not so extensive with other studies [7,8,[10][11][12][13][14][15][16]. It may be caused by unique provenance 1, 2, 3, 12, 14, 15, 16, and 22, see Table 2).…”
Section: Discussionmentioning
confidence: 85%
“…Several expression microarray studies have been performed for prognostic purposes in primary NMIBC, but none has shown sufficient clinical evidence to clinical usage. Most of them are based on identification of genes in transgenic mouse models [10], specific bladder cancer cell lineages [11], biological material from advanced tumors comparing gene expression in invasive stage of tumor disease [12,13,14] or usage of different molecular biological methods [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray gene expression analysis by Dyrskjøt et al (2 ), for example, revealed stage-specific gene clusters whose expression pattern allowed a classification of bladder cancer into 3 distinct histopathological groups: noninvasive Ta tumors, invasive T1 tumors, and T2-T4 tumors. However, validation of these consolidated findings via reverse transcription quantitative-PCR (RT-qPCR) 5 failed although the same sample material was used (3 ). The statistical basis, the RNA isolation procedure, and the stability of PCR amplicons, as well as the amount and particularly the quality of RNA, are some factors that influence the outcome of gene expression studies.…”
mentioning
confidence: 99%